An Expert System for Predicting Distribution and Consumption of Irrigation Water in a Paddy Irrigation Scheme - Daud, Mohamed (1994)
PADI_EX (Paddy Irrigation Expert), an expert system (ES) to predict the state of irrigation water distribution and consumption at an Irrigation Service Unit (ISU) level during off-season planting in a paddy irrigation scheme with double cropping was developed through a combination of interviews with field experts and formal field research. The purpose of the interviews was to identify and describe the problem domains and get the experts opinions on the problems that would be studied at field level in order to translate the experts knowledge into a more numerical form or specific rules that could then be incorporated into the ES. The raw data of the field studies were stored in databases and can be updated and referred to through the ES. The possible roles for PADI_EX areas advisor and peer system for better water management in a continuous and plot-to-plot paddy irrigation scheme.